Pengaruh Problem Based Learning dan Pendekatan CTL Berbasis ESD Terhadap Kemampuan Berpikir Kritis Dalam Pembelajaran Hybrid di Era New Normal - Amatulloh Mufida; Jun Surjanti; Waspodo Tjipto Subroto; Agus Widiono (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2022)
Activities inlearning hybrid in the new normal era, students' critical thinking skills at SMA Negeri 16 Surabaya have not been achieved optimally. The purpose of this study is to analyze the influence of the application of themodel Problem Based Learning and the ESD-based CTL approach on critical thinking skills inlearning hybrid in the new normal era. The type of approach in this research is quantitative while the type of research is causal associative. The sample used as many as 78 students from 97 students of class X Social Sciences SMA Negeri 16 Surabaya obtained through the slovin formula. The data collection stage in the study was carried out through theinstrument items pretest and posttest and for data analysis was carried out using the SPSS-24 application. Based on the analysis of the research results that there are significant differences in the effect of the application of themodel problem based learning and the ESD-based CTL approach on students' critical thinking skills. Models and approaches to learning are one of the important factors to improve critical thinking skills and based on the findings of researchers thatmodels problem-based learning and ESD-based CTL approaches affect students' critical thinking skills inlearning hybrid in the new normal era. DOI: https://dx.doi.org/10.17977/UM014v15i12022p009